Stigmatization and Social Support of Pregnant Women With HIV or Syphilis in Eastern China: A Mixed-Method Study - Zhang, Xiaohui; Wang, Xiaoyan; Wang, Hong; He, Xinmei; Wang, Xinyu (Frontiers in Public Health, 2022)
Background: Stigmatization and poor social support are challenges faced by individuals living with HIV or sexually transmitted disease, which can have a profound negative impact on their healthcare. Mother-to-child transmission of either HIV or syphilis can lead to adverse maternal and fetal adverse outcomes. The aim of this study was to investigate stigmatization and social support of pregnant women with HIV or syphilis in eastern China. Methods: This was an explanatory sequential mixed-method study conducted in Zhejiang province, China in 2019. Stigmatization, social support and associated factors toward HIV or syphilis were evaluated using questionnaires. The Social Support Rating Scale was used to evaluate social support, a score less than 25% was defined as poor social support. Logistic regression model was used to explore the association between stigmatization and poor social support. Results: A total of 448 women (HIV positive, N=93; syphilis, N=355) were recruited in this study. Higher stigmatization was observed in pregnant women with HIV compared to those with syphilis (53.76% vs. 24.36%, p<0.001), and poorer social support was observed in women with HIV compared with those with syphilis (40.86% vs. 19.86%, p<0.001), with significant distributions of the total social support scores (Z=-1.976, p=0.048) , and scores on objectivity (Z=-2.036, p=0.042) and subjectivity (Z=-2.500, p=0.012). Similar social support among HIV or syphilis pregnant women was observed in medical healthcare facilities. In multivariable logistic model analysis, stigmatization (ORadj=2.927; 95%CI, 1.714–4.996; p<0.001) and ethnic minority (ORadj=2.373; 95%CI, 1.113–5.056; p=0.025) were negatively associated with social support. Interestingly, employment status was associated with improved social support (ORadj =0.345; 95%CI, 0.180–0.662; p=0.001). Conclusion: Stigmatization among pregnant women with HIV or syphilis remains high. We demonstrated that stigmatization was a significant predictor of low social support in pregnant women with HIV or syphilis. The support shown in medical facilities was similar toward pregnant women with HIV or syphilis. Implementation of stigmatization eradication and social support strategies targeting pregnant women with HIV or syphilis may therefore improve the dual elimination of mother-to-child transmission service.